Determination of rifaximine in milk of dairy cows using High Pressure Liquid Chromatography (HPLC) - íngeles Manjarrez, José Luis; ívila Téllez, Salvador; Rosiles Martínez, René; Fuentes Hernández, Víctor Octavio (Revista Científica de la Facultad de Ciencias Veterinarias, 2012)
The objective of this work was to develop and validate a High Performance Liquid Chromatography (HPLC) method for the detection of rifaximine in milk of dairy cows. HPLC grade methanol and ammonium acetate as the Mobile phases, a C18 column and a UV detector were used. Validation of the method was carried out using standards of pure rifaximine dissolved in methanol. It was observed that linearity was above 0.99 of r2. Average recovery was above 54%. A high specificity was evident and interfering substances did not affect the results. The minimum limit of detection was 30 ng/mL and the quantification limit was 150 ng/mL. For the kinetic analysis the antibiotic (100 mg) was infused into the udder of two lactating cows. For one cow a coefficient of depuration of 0.0122, with a half life of 24.6 hours and 8.65 g/mL*h (* = multiplied by), Area Under the Curve (AUC) was observed. For the second cow the coefficient of depuration was 0.00749 with a half life of 23.9 hrs and 7.75 Âµg/mL*h was detected. In the field rifaximine (100 and 200 mg) was infused into the udder of 20 cows at the end of the lactation period; thereafter samples were obtained from treated cows and it was observed that rifaximine was not detected in calostrum and milk of treated cows, using the described HPLC method. It was concluded that the use of HPLC is a reliable method to detect rifaximine in milk and colostrum of cows treated with the antibiotic.